Leadership Communication Model of the Executive Student Council of the Faculty of Social Sciences, State Islamic University of North Sumatra - Elryan Adha, Dwiki; Azhar, Anang Anas (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
This study aims to explore and analyze the leadership communication model implemented by the Student Executive Board (DEMA) of the Faculty of Social Sciences at the State Islamic University of North Sumatra (UINSU). This research is crucial as effective communication is key to strengthening leadership and enhancing the performance of student organizations in a dynamic academic environment. By understanding the dynamics of communication in the context of student leadership, it is hoped that recommendations can be found to improve leadership effectiveness and strengthen relationships between students and the academic community and broader society. The method used in this study is qualitative with a qualitative descriptive approach. Data collection techniques include in-depth interviews with DEMA members, participatory observation in DEMA meetings and activities, and analysis of official documents such as meeting minutes and activity reports. Data analysis was conducted using thematic analysis to identify main themes, and data validity was examined through data triangulation, credibility, transferability, dependability, and confirmability techniques. The results show that the Leadership Communication Model of DEMA-FIS UINSU emphasizes openness, constructive feedback, and adaptability to situations and member needs. This model encompasses various critical aspects of leadership communication, including how leaders communicate, how messages are conveyed, and how they are received and understood by organization members. However, the model also faces challenges, including gaps between the vision conveyed by leaders and members' understanding and engagement, as well as challenges in achieving deep consensus or overcoming differing opinions that may arise. Overall, this study provides valuable insights into the strengths and limitations of the leadership communication model applied in DEMA-FIS UINSU, and offers recommendations for further improvement and development in student leadership practices.